Bemisia tabaci MED Population Density as Affected by Rootstock-Modified Leaf Anatomy and Amino Acid Profiles in Hydroponically Grown Tomato - Žanić, Katja; Dumičić, Gvozden; Mandušić, Marija; Vuletin Selak, Gabriela; Bočina, Ivana; Urlić, Branimir; Ljubenkov, Ivica; Bučević Popović, Viljemka; Goreta Ban, Smiljana (Frontiers in Plant Science, 2018)
Bemisia tabaci is one of the most devastating pests in tomato greenhouse production. Insecticide resistance management for B. tabaci requires a novel approach that maximizes nonchemical methods for pest control. The aim of this study was to test the effects of rootstocks on B. tabaci populations in hydroponically grown tomato plants. In order to contribute to the better understanding of the mechanisms defining the attractiveness of plant to the aerial pest, the effects of rootstocks on leaf anatomy and the amino acid composition of phloem sap were assessed. A two-factorial experimental design was adopted using cultivars (rootstock cultivars and Clarabella) grown as either nongrafted or grafted with cultivar Clarabella as a scion. The rootstock cultivars included Arnold, Buffon, Emperador, and Maxifort. A reduction in B. tabaci density was observed using all rootstock cultivars. The number of adult individuals per leaf was 2.7-5.4 times lower on rootstock cultivars than on Clarabella. The number of large nymphs per square centimeter was at least 24% higher on nongrafted Clarabella compared with all other treatments. The leaf lamina thickness and mesophyll thickness were lower in self-grafted Clarabella than in nongrafted or in one grafted on rootstock cultivars; however, the extent of this reduction depended on the rootstock. The leaves with thinner laminae were generally less attractive to B. tabaci. Eighteen amino acids were detected in the exudates of phloem sap. In all treatments, the most abundant amino acid was γ-aminobutyric acid (GABA), followed by proline, serine, alanine, and histidine. The scion cultivar Clarabella was the most attractive to B. tabaci and had a higher content of leucine than did rootstock cultivars, and a higher content of lysine compared to Buffon and Maxifort. The features modified by rootstock such are changes in leaf anatomy can affect the attractiveness of plants to B. tabaci. Thus, the grafting of tomato could constitute a valuable tool in an integrated management strategy against this aerial pest.